2012
DOI: 10.1007/s10658-012-0062-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of susceptibility of an olive progeny (Picholine x Meski) to olive leaf spot disease caused by Fusicladium oleagineum

Abstract: Forty five descendants from a crossing between olive cultivar Picholine de Languedoc and the local cultivar Meski were evaluated for their susceptibility to olive leaf spot (Fusicladium oleagineum) in field and laboratory studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Reports indicated that trichome can defence against bacterial pathogens by several means such as reducing and/or hindering the water film formation on the leaf surface, making difficult to germinate spore and subsequent bacterial multiplication (Nicks & Rubiales 2002;Medeiros et al 2004;Kang et al 2010). Moreover, Rhouma et al (2013) reported that resistant olive hybrids were characterised by a high number of trichomes in comparison with susceptible cultivars for olive leaf spot disease.…”
Section: Discussionmentioning
confidence: 99%
“…Reports indicated that trichome can defence against bacterial pathogens by several means such as reducing and/or hindering the water film formation on the leaf surface, making difficult to germinate spore and subsequent bacterial multiplication (Nicks & Rubiales 2002;Medeiros et al 2004;Kang et al 2010). Moreover, Rhouma et al (2013) reported that resistant olive hybrids were characterised by a high number of trichomes in comparison with susceptible cultivars for olive leaf spot disease.…”
Section: Discussionmentioning
confidence: 99%
“…Other biological and metabolic barriers could also prevent the successful extraction of thylakoids in plant species characterized by very thick and leathery leaves such as conifers, palm trees, or olive trees ( Olea europaea ) [ 37 ], which exhibit an elevated wax content in the cuticle. Nevertheless, the optimized protocol works well on the various plant species tested in this study, particularly Posidonia oceanica , but also Vitis vinifera and Quercus pubescens , which are very rich in polyphenols.…”
Section: Discussionmentioning
confidence: 99%
“…The resistance of olive to OLS has been associated with both physical and chemical factors. Among the physical factors, trichome density and cuticle thickness have been recognized as the most important [ 40 ], while among chemical parameters, phenolic compounds are those determining the resistance of olive to OLS [ 41 ]. Olive leaf and olive fruit extracts are dominated by a vast variety of phenolic compounds, such as oleuropeine, rutin, tyrosol and others, with some of them exhibiting strong antifungal properties [ 42 ].…”
Section: Discussionmentioning
confidence: 99%